Factors affecting the ageing of polymer composite: A state of art - Gupta, Ayushi; Kumar, Narendra; Sachdeva, Anish (Polymer degradation and stability, 2024)
•The article explores the effect of various factors on ageing of polymer composites.•Focuses the significance of practical tools for optimizing durability, including experimental and accelerated aging methods.•Discusses about reinforcing materials to enhance the overall performance and resilience of polymer composites. Polymer composites have become indispensable in modern engineering applications, presenting a unique blend of qualities, including lightweight design, high strength, and corrosion resistance. Despite the inherent strength of these materials, their sustained performance is intricately linked to the various factors influencing the ageing process. It delves into the realms of general degradation, the impact of environmental conditions, and the role of fabrication & and synthesis methods. Emphasizing the pivotal role of aging in defining the reliability and durability of these materials, the research unfolds critical insights. Beyond elucidating the aging factors, the paper navigates through various experimental methodologies and accelerated aging techniques. These insights provide tangible strategies to augment the long-term performance of polymer composites by incorporating reinforcements such as nanofiller or nano clays with polymer matrix. By consolidating and advancing the current knowledge base, this study serves as a valuable resource for engineers and researchers, offering practical tools to optimize the durability of polymer composites across a broad spectrum of applications. [Display omitted]